Social Work Services for Persons with Disabilities in Nigeria: A Qualitative Inquiry - Amadasun, Solomon (International Journal of Social Sciences Perspectives, 2020)
The challenges experienced by persons with disabilities (PWDs) are real and profound, requiring the attention of social workers. Unless interventions are aimed at eliminating the broad range of society-imposed barriers, recovery efforts would continue to be undermined. The focus of this study is to share the experiences of social workers regarding their services to PWDs in Nigeria. Using a social constructivist theory, semi-structured interviews were conducted with social workers in one organization providing services to PWDs in Nigeria and the results were subjected to thematic analysis. Findings show that social work services provided to PWDs are inadequate in line with the person-in-environment focus of the social work profession Application: While this research relates to practitioners in one organization, findings have broader implications for professionals and policymakers in Nigeria. In this regard, suggestions are offered to the Nigerian political leadership as well as to social work practitioners in order to ensure that comprehensive services are offered to this underserved and undervalued population.